HIDROGEOLOGIA DO MUNICÍPIO DE JUAZEIRO DO NORTE, ESTADO DO CEARÁ - Lopes, Cícero Roberto Martins; Dias, Francisco Wladiston Cordeiro; Cavalcante, Itabaraci Nazareno; Souza, Ana Katiuscia Pastana de (Águas Subterrâneas, 2001)
Resumo não disponível.